Kinematic analysis of anterior cruciate ligament reconstruction in total knee arthroplasty - Liu, Hua-Wei (Am J Transl Res, 2016)
Background: This study aims to retain normal knee kinematics after knee replacement surgeries by reconstructing anterior cruciate ligament during total knee arthroplasty. Method: We use computational simulation tools to establish four dynamic knee models, including normal knee model, posterior cruciate ligament retaining knee model, posterior cruciate ligament substituting knee model, and anterior cruciate ligament reconstructing knee model. Our proposed method utilizes magnetic resonance images to reconstruct solid bones and attachments of ligaments, and assemble femoral and tibial components according representative literatures and operational specifications. Dynamic data of axial tibial rotation and femoral translation from full-extension to 135 were measured for analyzing the motion of knee models. Findings: The computational simulation results show that comparing with the posterior cruciate ligament retained knee model and the posterior cruciate ligament substituted knee model, reconstructing anterior cruciate ligament improves the posterior movement of the lateral condyle, medial condyle and tibial internal rotation through a full range of flexion. The maximum posterior translations of the lateral condyle, medial condyle and tibial internal rotation of the anterior cruciate ligament reconstructed knee are 15.3 mm, 4.6 mm and 20.6 at 135 of flexion. Interpretation: Reconstructing anterior cruciate ligament in total knee arthroplasty has been approved to be an more efficient way of maintaining normal knee kinematics comparing to posterior cruciate ligament retained and posterior cruciate ligament substituted total knee arthroplasty.